2003
DOI: 10.3748/wjg.v9.i11.2484
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis in chronic viral hepatitis: An ultrasonographic study

Abstract: There are different ultrasonographic predictors for the evaluation of hepatic inflammation grade and fibrosis stage of chronic hepatitis. Both ultrasonography and serology have their own advantages and disadvantages in the evaluation of liver fibrosis and compensated liver cirrhosis. Combined application of the two methods is hopeful to improve the diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 20 publications
0
31
0
1
Order By: Relevance
“…Hung et al [21] evaluated the validity of US in diagnosis of cirrhosis with a diagnostic sensitivity of liver cirrhosis of 0.775 and a specificity of 0.92 in patients with HBV infection. Zheng et al [22] studied the value of US in evaluation of liver fibrosis and compensated cirrhosis in comparison with serology and histology and found that hepatic parenchymal echo pattern, liver surface and thickness of gallbladder wall are three independent predictors of liver fibrosis. The diagnostic accuracy of US for compensated cirrhosis is 80.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Hung et al [21] evaluated the validity of US in diagnosis of cirrhosis with a diagnostic sensitivity of liver cirrhosis of 0.775 and a specificity of 0.92 in patients with HBV infection. Zheng et al [22] studied the value of US in evaluation of liver fibrosis and compensated cirrhosis in comparison with serology and histology and found that hepatic parenchymal echo pattern, liver surface and thickness of gallbladder wall are three independent predictors of liver fibrosis. The diagnostic accuracy of US for compensated cirrhosis is 80.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic fibrogenesis is often associated with hepatocellular necrosis and inflammation accompanied by repair processes [26,27] . Kupffer cells were shown to be a critical mediator of the inflammatory and fibrogenic responses during CCl 4 -mediated Yuan GJ et al Pioglitazone on rat hepatic fibrosi 1049 B A liver damages [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Zhong and others observed that this increased thickness and echogenicity of the gall bladder walls is related to the progression of fibrosis in patients with chronic viral hepatitis. 27 In the population studied, a patent paraumbilical vein was seen in 2% of cases, which can be explained by a recent diagnosis. Most patients were asymptomatic.…”
Section: Assessment Of Fibrosis In Patients With Hepatitis Cmentioning
confidence: 99%